2013
DOI: 10.1177/0300060513487642
|View full text |Cite
|
Sign up to set email alerts
|

Indoleamine 2,3-dioxygenase levels at the normal and recurrent spontaneous abortion fetal–maternal interface

Abstract: Objectives: To localize indoleamine 2,3-dioxygenase (IDO) mRNA and protein and to undertake a functional study at the first trimester fetal-maternal interface in order to determine whether the distribution and function of IDO are related to recurrent spontaneous abortion (RSA). Methods: Women undergoing legal pregnancy termination and women with RSA participated in this prospective study. Immunohistochemistry and real-time reverse transcription-polymerase chain reaction were used to analyse levels of IDO prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 45 publications
3
33
0
1
Order By: Relevance
“…Though a review of the impact of kynurenine metabolism on the peripheral immune system is beyond the scope of the current review, it is important to keep this function of the kynurenine system in mind when considering the therapeutic potential of this pathway. An important role of IDO in immunosuppression and tolerance has been demonstrated during pregnancy, autoimmunity, resistance to tumors, and tolerance to allografts (Mellor and Munn, 2004; Barth and Raghuraman, 2012; Ban et al, 2013). Thus, therapeutic interventions involving the KP must be approached cautiously to examine the potential consequence on immunomodulatory actions.…”
Section: Therapeutic Potential and Immune Interactions By The Kynurenmentioning
confidence: 99%
“…Though a review of the impact of kynurenine metabolism on the peripheral immune system is beyond the scope of the current review, it is important to keep this function of the kynurenine system in mind when considering the therapeutic potential of this pathway. An important role of IDO in immunosuppression and tolerance has been demonstrated during pregnancy, autoimmunity, resistance to tumors, and tolerance to allografts (Mellor and Munn, 2004; Barth and Raghuraman, 2012; Ban et al, 2013). Thus, therapeutic interventions involving the KP must be approached cautiously to examine the potential consequence on immunomodulatory actions.…”
Section: Therapeutic Potential and Immune Interactions By The Kynurenmentioning
confidence: 99%
“…The constitutive expression of HLA-G on these cells plays an important role in inducing immunotolerance by inhibiting cytotoxicity mediated by natural killer (NK) cells [3-6] and T-cells [7-9]. In addition, the finding of decreased protein and mRNA levels of indoleamine 2,3-dioxygenase (IDO) in the placenta and decidua from recurrent spontaneous abortuses suggests an important role for IDO in the maintenance of normal pregnancy [10]. It has also been suggested that during pregnancy the programmed cell death-1 (PD-1) pathway can modify the maternal decidual lymphocyte cytokine secretion facilitating immune suppression[11].…”
Section: Introductionmentioning
confidence: 99%
“…They are poorly characterized with regard to their distinctive phenotype, anatomical localization, and function, however, appear to be important in embryo implantation and, most likely, in regulating placenta-specific tolerance to the semiallograft [28,40,41]. There are several reports documenting that DCs conditioned by trophoblasts in vitro fail to promote expansion of T cells or stimulate differentiation of regulatory T cells, which was mainly attributed to the production of soluble mediators such as IDO, TSLP,33,42,43]. Though we cannot exclude that soluble mediators may contribute in DC silencing by choriocarcinoma cells in our system, these are unlikely to contribute in cocultures involving CHO transfectants, which would only release hamster-specific factors not triggering a response in human target cells.…”
mentioning
confidence: 99%